A terhelt vallomásának szerepe a büntetőeljárásban - Mező, Annamária (Debreceni Jogi Műhely, 2012)
According to our criminal procedure rights which are in force at persent we have to keep in mind the equality of the tools of argumentation and tehir parity. In the sense of this thesis all the proofs must be measured with the same weight excluding the fact that we make distinction between their values, „straingths” from any aspects.Examining the practise of criminal produred law we can see that they are in total contrast, namely in the balance of argumentative tools there is still an argumentative tool of personal nature, which breaks this order, this parity. This is nothing else but the statement of the accused person.When I chose this topic I thought of the above mentioned ambivalent consideration of the ambivalent statement of the accused person.First I would like to outline briefly the connection between the confessions of the accused person and the other argumentative tools, then I want to examine the fact that the accused person must be warned to their right to silence in connection with the „Miranda – decision”.After that I would like to describe the right to statement and to silence of the accused as well as the special procedural froms which are in force concerning my topic.